Strategi Pengadilan Agama Dan Persiapan Personal Hakim Dalam Menyelesaikan Sengketa Ekonomi Syari’ah - Agus Silachi Adi P (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2018)
Shari'ah economic disputes have become the absolute authority of the Religious Court so that they have new duties as well as challenges to answer the emerging public doubts about the readiness of the Religious Courts and their judges' personalities. The new authority granted under the Law Article 49 Number 3 of 2006 concerning Religious Courts emphasizes that the Religious Courts have the duty and authority to examine, try and resolve sharia economic disputes. Absolute authority in resolving shari'ah economic disputes is very appropriate, but it needs institutional strengthening, strengthening human resources, then needs to be sustained immediately by the issuance of the Religious Courts procedural law. Preparing HR for judges by conducting trainings on sharia economics because judges will understand more about the economic problems that will arise so that if there are cases that enter the panel of judges, they are ready to complete, increasing the collection of library books about Shari'ah economics and for the Religious Courts themselves have a lot of relationships with universities and research institutions.